HUBUNGAN ANTARA MINAT MENJADI PERAWAT DENGAN PRESTASI BELAJAR DI FAKULTAS ILMU KESEHATAN UNIVESITAS ISLAM ASSYAFI’IYAH JAKARTA - Atiyah NA; Fany Firmansyah (Afiat, 2016)
Introduction: Someone who wants to be a nurse, should have a high interest. so he will earnestly study,seen by the behavior of such diligent study, diligent reading, tasks and others. Results of learning theshape of a good performance. The purpose of this study was to determine the relationship betweeninterest in becoming a nurse with the achievement of students of the Faculty of Health SciencesUniversity of Islam As-Shafi'ites Jakarta. Methods: Type a descriptive correlative study, samplenya asmany as 59 students. Research instruments using questionnaires and documentation. Univariateanalysis of data put (%) and bivariate analysis wear Chi-Square test α = 5%. Result: The high interestin becoming a nurse 55.9% and student achievement is good enough to 52.5%. Value Chi-Square (X2)= 7.861> 3.841 (X2 table) means that there is a relationship. Conclusion: there is a fairly strongcorrelation between interest in becoming nurses 0.485 and the learning achievement Suggestion: inorder to further enhance student learning spirit, pray before the course begins and parents bettersupport their interests.